Formação de professores de educação física da Universidade Estadual de Londrina: tradução do projeto curricular pelos professores - Cesário, Marilene (2008)
The curricular reformulation process which is established for every graduation course at National institutions of Higher Education, has the instructions for these curricular modifications in the National Curriculum Guideline CP01 and CP02 of 2002. Considering the course of Physical Education at UEL as a reference, we can realize that the curricular project of this course was installed in 2005 and it treats specifically the Physical Education teacher s education Licentiate degree. Recognizing the importance of the initial formation's task at teachers' professionalization and knowing that the possible changes in school institutions depend on this initial formation, this inquiry intend to analyze how teachers of the Physical Education course have translated the principles and guidelines which direct this curricular project into pedagogic practice. The main issue in this inquiry is teachers educators, because when they propose and resolve changes in the teachers' formation, they are also involved in a learning process and professional development. The specific elaborated goals were the following: a) Identify and analyze boundaries, challenges and difficulties found by teachers during the curricular project establishment; b) Describe and analyze teachers' initial learning derived from the curricular project establishment based on the perspective of the participant teachers; c) Identify, based on the narrative of the interviewee, that knowledge is recognized as important for the Physical Education teachers' education. We voted for a narrative inquisition in the current study, because it is understood that it characterizes the human experience phenomenon which is built during personal and professional life. A Semi-structured Interview was taken as a source for the data collection. This Interview was made with a teacher group that took part in the first year-Licensure establishment UEL (2005). Also, a Thematic Analysis was taken to treat and analyze the collected data. The results have showed the necessity for an association between school institution and university as one of the possibilities of teachers' professional development. The initial formation must approach the educative practice into school and must become an investigation field in a process of collaboration among different professionals.